Optimal water allocation method for joint operation of a reservoir and pumping station under insufficient irrigation - Cong Wei; Jilin Cheng; Yi Gong; Zhihao Gong (Water Supply, 2021)
To address the problem of optimal allocation of water resources in water shortage areas, a reservoir and a pumping station water resource optimal scheduling model under the condition of insufficient irrigation is proposed. The model takes the maximum relative yield of crops as the objective function, the amount of water supplied, water spilled and water replenished as decision variables, the total amount of water supplied by the system, the water right of the pumping station and the operation criteria as constraints, and uses a dynamic programming method to solve the model. The optimal water supply and water spill process of the irrigation reservoir and the optimal water replenishment process of a pumping station during the entire growth period of dry crops were obtained. Moreover, under the conditions of 50 and 75% probability of exceedance, the optimized relative yields of crops increased by 17.1% and 19.6%, respectively. The results show that ensuring the optimal operation of joint water source projects can achieve the optimal allocation of limited water resources, and improve the relative yield of crops in irrigation areas, which has important guiding significance for the planning and management of water resources in similar irrigation areas. HIGHLIGHTS An optimal water allocation model for the joint operation of a reservoir and pump station in arid areas is established, considering regional water rights.; An operation rule for a reservoir is integrated into the recursive process of the dynamic programming to solve the model.; The penalty function method is introduced into the dynamic programming to deal with the constraint of water rights.;